Modified volumetric modulated arc therapy technique with reduced planning and treatment time for craniospinal irradiation utilising two isocentres - Minh Nguyen; Thu Dang; Liz Deegan; Kelsie Henry; Scott Jones; Andrew Pullar; Robyn Cheuk; Adrian Gibbs; Lucy Sim; Catriona Hargrave (Journal of Medical Radiation Sciences, 2022)
Abstract Introduction Paediatric patients (individuals below 18 years of age) requiring cranial‐spinal irradiation (CSI) at our institution are commonly planned and treated using a three isocentre (3‐ISO) volumetric modulated arc therapy (VMAT) technique. A modified two isocentre (2‐ISO) VMAT technique was investigated with the aim to improve workflow and reduce planning and treatment time. Methods Five CSI paediatric patients previously treated with a 3‐ISO VMAT technique were retrospectively replanned using a 2‐ISO VMAT technique. The 2‐ISO VMAT plans were reviewed and approved by a radiation oncologist (RO) before undergoing patient‐specific quality assurance (QA) procedures, performed by a radiation oncology medical physicist (ROMP). Planning target volume (PTV) coverage, organ‐at‐risk (OAR) dose as well as planning and treatment durations of the first five patients utilising 2‐ISO technique were compared with 3‐ISO technique. Results The average percentage difference in PTV coverage by 95% reference dose between the 2‐ISO and 3‐ISO is 0.14%, and the average difference in OAR median dose is 0.68 Gy. Conformity and homogeneity indices have the same averages at 1.18 and 0.4 respectively. Patient‐specific physics QA results were all comparable with the 3‐ISO averages at 98.84% and the 2‐ISO at 98.71%. Planning duration for the 2‐ISO was reduced by up to 75%, and daily treatment duration was reduced by up to 50%. Of all the previously treated CSI patients using a 3‐ISO technique, 45% were suitable for the 2‐ISO technique. Conclusion The 2‐ISO VMAT technique provided comparable dose distribution based on PTV coverage, OAR dose and plan metric indices. Reduced planning and treatment duration with the 2‐ISO technique facilitated improved workflow with decreased sedation time for paediatric patients requiring a general anaesthesia.